2009
DOI: 10.1007/s12618-009-0007-2
|View full text |Cite
|
Sign up to set email alerts
|

A clinical review of outcomes of the Multimodal treatment study of children with attention-deficit/hyperactivity disorder (MTA)

Abstract: Over the past decade, the MTA has provided a bewildering wealth of data (70 peer-reviewed articles) addressing treatment-related questions for children with attention-deficit/hyperactivity disorder (ADHD); however, the take-home messages for clinicians may not always be clear. Therefore, this article reviews key findings, including relative benefits of medication and behavioral treatments, long-term effects at two and three years, treatment mediators and moderators, preliminary delinquency and substance use ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 44 publications
0
15
0
1
Order By: Relevance
“…However, it was noted that the children in the MTA medication treatment arms received larger doses of medication for a longer period of time and medication management by a clinical pharmacist occurred monthly, compared to the communitytreated group where this did not occur. 11,52,53 In the 8-year follow-up study, there appears to be a loss of sustained effects of medication after 2 years. Since the long-term follow-up was done "naturally" and without randomization, it is very difficult to know if sustained clinical benefit may have been maintained with intensive medication management plus behavioral therapy.…”
Section: Multimodal Treatment Study Of Children With Attention-deficimentioning
confidence: 99%
“…However, it was noted that the children in the MTA medication treatment arms received larger doses of medication for a longer period of time and medication management by a clinical pharmacist occurred monthly, compared to the communitytreated group where this did not occur. 11,52,53 In the 8-year follow-up study, there appears to be a loss of sustained effects of medication after 2 years. Since the long-term follow-up was done "naturally" and without randomization, it is very difficult to know if sustained clinical benefit may have been maintained with intensive medication management plus behavioral therapy.…”
Section: Multimodal Treatment Study Of Children With Attention-deficimentioning
confidence: 99%
“…Although we recognize differences between the disorders, like central hypersomnia, ADHD is primarily treated with medication but children with ADHD also benefit greatly from psychosocial and educational interventions designed to improve cognitive development, and metacognition. 64 Such behavioral interventions reduce cognitive impairment and improve health, social development, school performance, quality of life, and success in adulthood among children with ADHD. The large randomized MTA study found that both treatment with medication alone and the combined treatment with medication and behavioral interventions result in the greatest improvement in ADHD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that assignment to a medication treatment arm continued to confer some additional benefit after randomization was discontinued for up to 3 years [11]. After 3 years, the effects of the 14-month randomization were no longer evident.…”
Section: Symptom Reductionmentioning
confidence: 99%